Temporalités en tension de parents de jeunes enfants confinés - Pierre Ratinaud; Anne Dupuy; Alice Moscaritolo; Julie Renard; Chantal Zaouche Gaudron (Temporalités)
The unusual context of lockdown linked to the Covid-19 pandemic was conducive to a delegation of temporalities related to early childhood by the state, which seemed important to study, especially in families with children from birth to six years old. How did the pandemic modify daily temporalities related to care, educational, digital, play and school practices? How have these everyday temporalities been (re)organized in day-to-day life?This article is based on an online questionnaire survey implemented during the first lockdown in France. The analysis, carried out with Iramuteq, focuses on the free expression of parents (n = 490) and that which they lend to their young children (n = 226) and their relationship with other variables such as resource and study levels, housing, professional activity and parental gender.By presenting four temporalities in their discourse (the professional temporality, an “enchanted parenthesis”, the lack of social relations and the rhythms of daily life), the analysis shows that the family unit has had to adapt daily temporalities and invent new rhythms to pursue professional occupations, to take care of young children, to transform oneself into a “school teacher”, to keep the house going (shopping, housework, cooking, leisure activities), and to compensate for missing social relationships.